The Implementation of Women’s Jurisprudence: Realization of Learning Kitab in Islamic Boarding School Al Fattah Kartasura - Sri Lestari; Alifia Nur Aini (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2023)
Islamic boarding schools are places to learn and develop the knowledge gained by students. Islamic boarding schools also emphasize the science of jurisprudence which requires practice in daily life to a certain extent. The aim of this research is to explain the implementation of women's jurisprudence based on books studied in lessons at the Al-Fattah Islamic Boarding School, Kartasura, Sukoharjo, Central Java. In this case, women's jurisprudence is limited to menstruation, childbirth and istiadhah, in relation to marriage law. This research is a qualitative descriptive study with data in the form of documents (in the form of books used in learning), interview results (to students and ustadz/ustadzah) and observation results (learning process). The data validation technique uses triangulation of theory, methods and data. The data analysis technique uses the Miles and Huberman interactive model. The research results show that learning about menstruation, postpartum and istiadhah helps students to understand and apply the teachings according to the understanding obtained. The relationship between marriage and menstruation, postpartum and istiadhah can help students understand how to deal with their situation as a wife and husband. The novelty of the research results obtained lies in the students' understanding that when menstruating, a woman cannot be divorced by her husband.